Thusin, a Novel Two-Component Lantibiotic with Potent Antimicrobial Activity against Several Gram-Positive Pathogens - Xin, Bingyue; Zheng, Jinshui; Liu, Hualin; Li, Junhua; Ruan, Lifang; Peng, Donghai; Sajid, Muhammad; Sun, Ming (Frontiers in Microbiology, 2016)
Due to the rapidly increasing prevalence of multidrug-resistant bacterial strains, the need for new antimicrobial drugs to treat infections has become urgent. Bacteriocins, which are antimicrobial peptides of bacterial origin, are considered potential alternatives to conventional antibiotics and have attracted widespread attention in recent years. Among these bacteriocins, lantibiotics, especially two-component lantibiotics, exhibit potent antimicrobial activity against some clinically relevant Gram-positive pathogens and have potential applications in the pharmaceutical industry. In this study, we characterized a novel two-component lantibiotic termed thusin that consists of Thsα, Thsβ and Thsβ' (mutation of Thsβ, A14G) and that was isolated from a B. thuringiensis strain BGSC 4BT1. Thsα and Thsβ (or Thsβ') exhibit optimal antimicrobial activity at a 1:1 ratio and act sequentially to affect target cells, and they are all highly thermostable (100°C for 30 min) and pH tolerant (pH 2.0 to 9.0). Thusin shows remarkable efficacy against all tested Gram-positive bacteria and greater activities than two known lantibiotics thuricin 4A-4 and ticin A4, and one antibiotic vancomycin against various bacterial pathogens (Bacillus cereus, Listeria monocytogenes, Staphylococcus aureus (MRSA), Staphylococcus sciuri, Enterococcus faecalis, and Streptococcus pneumoniae). Moreover, thusin is also able to inhibit the outgrowth of Bacillus cereus spores. The potent antimicrobial activity of thusin against some Gram-positive pathogens indicates that it has potential for the development of new drugs.